The CD4+ T Cell Response to Human Cytomegalovirus in Healthy and Immunocompromised People - Lim, Eleanor Y.; Jackson, Sarah E.; Wills, Mark R. (Frontiers in Cellular and Infection Microbiology, 2020)
While CD8+ T cells specific for human cytomegalovirus (HCMV) have been extensively studied in both healthy HCMV seropositive carriers and patients undergoing immunosuppression, studies on the CD4+ T cell response to HCMV had lagged behind. However, over the last few years there has been a significant advance in our understanding of the importance and contribution that CMV-specific CD4+ T cells make, not only to anti-viral immunity but also in the potential maintenance of latently infected cells. During primary infection with HCMV in adults, CD4+ T cells are important for the resolution of symptomatic disease, while persistent shedding of HCMV into urine and saliva is associated with a lack of HCMV specific CD4+ T cell response in young children. In immunosuppressed solid organ transplant recipients, a delayed appearance of HCMV-specific CD4+ T cells is associated with prolonged viremia and more severe clinical disease, while in haematopoietic stem cell transplant recipients, it has been suggested that HCMV-specific CD4+ T cells are required for HCMV-specific CD8+ T cells to exert their anti-viral effects. In addition, adoptive T-cell immunotherapy in transplant patients has shown that the presence of HCMV-specific CD4+ T cells is required for the maintenance of HCMV-specific CD8+ T cells. HCMV is a paradigm for immune evasion. The presence of viral genes that down-regulate MHC class II molecules and the expression of viral IL-10 both limit antigen presentation to CD4+ T cells, underlining the important role that this T cell subset has in antiviral immunity. This review will discuss the antigen specificity, effector function, phenotype and direct anti-viral properties of HCMV specific CD4+ T cells, as well as reviewing our understanding of the importance of this T cell subset in primary infection and long-term carriage in healthy individuals. In addition, their role and importance in congenital HCMV infection and during immunosuppression in both solid organ and haemopoietic stem cell transplantation is considered.